Effect of crocin on nitric oxide synthase expression in post-ischemic isolated rat heart - Mahdi Esmaeilizadeh; Mahin Dianat; Mohammad Badavi; Alireza Samarbaf-zadeh; Bahareh Naghizadeh (Avicenna Journal of Phytomedicine, 2015)
Objective: Oxidative stress damages cells and brings about the pathogenesis of ischemia/reperfusion injury. This study was carried out to investigate the preconditioning and cardio protective potential effects of crocin and vitamin E by the eNOS and iNOS express gene in ischemia/reperfusion in rats. Material & Methods: Male rats were divided into seven groups, namely: sham, control group and experimental groups treated with crocin(10, 20 and 40 mg/kg), vitamin E (100 mg/kg) and combination of crocin (40 mg/kg) with vitamin E (100 mg/kg) that were gavaged The heart was removed and relocated to a Langendorff apparatus and subjected to global ischemia and then the left ventricular end diastolic pressure (LVEDP) were measured as a hemodynamic parameter. Total RNA was extracted from heart frozen tissues. RT-PCR technique was performed by specific primers designed for nitric oxide gene and the results were assessed by agarose gel electrophoresis. Results: Results after ischemia and reperfusion showed that crocin 40 mg/kg produced a significant improvement of LVEDP as a mechanical function (P